Simple procedure for nutrient analysis of coffee plant with energy dispersive X-ray fluorescence spectrometry (EDXRF) - Tezotto, Tiago; Favarin, José Laércio; Neto, Ana Paula; Gratão, Priscila Lupino [UNESP]; Azevedo, Ricardo Antunes; Mazzafera, Paulo (FapUNIFESP (SciELO), 2013)
Nutrient analysis is used to estimate nutrient content of crop plants to manage fertilizer application for sustained crop production. Direct solid analysis of agricultural and environmental samples by energy dispersive X-ray fluorescence spectrometry (EDXRF) was chosen as alternative technique to evaluate the simultaneous multielemental quantification of the most important essential elements in coffee (Coffea arabica L.) plants. Inductively coupled plasma atomic emission spectrometry and certified reference materials made from leaves were used to calibrate and check the trueness of EDXRF method for the determination of the concentration of several nutrients in coffee leaves and branches. Fluorescence spectrometry proved to be advantageous and presented low cost as loose powder samples could be used. Samples collected from a field experiment where coffee plants were treated with excess of Ni and Zn were used to verify the practical application of the method. Good relationships were achieved between certified values and data obtained by EDXRF, with recoveries ranging from 82 to 117 %.
Keywords: Analytical procedure; Coffea arabica; Metal toxicity; Mineral nutrition